Supply Chain in the Construction Industry: Micro, Meso, Macro - Moh Nur Sholeh; Mochamad Agung Wibowo (JACEE (Journal of Advanced Civil and Environmental Engineering), 2020)
The construction industry is so fragmented that in its implementation many have resulted in increased costs, delays, and inefficiencies. But this fragmented can not be a reason not to innovate. One approach to the solution used is supply chain construction. The purpose of this study is to map supply chains micro, meso, and macro. This level is tiered from the bottom to the top level as the concept of supply chain management. The qualitative and quantitative research method was used to map and analyze supply chains for each level. The results showed the micro-level is the basis of the supply chain which can be measured by SCOR for example. The meso level focuses on the strength of construction companies. Construction company strategies framework contract and Enterprises Resource Planning (ERP). Macro-level includes supply chain accumulation from micro and meso. It is expected that at the macro level is the harmonization of supply chains between stakeholders, namely the government, contractors, suppliers, and distributors with good policy regulations.